“Beauty” premium for social scientists but “unattractiveness” premium for natural scientists in the public speaking market - Weilong Bi; Ho Fai Chan; Benno Torgler (Humanities & Social Sciences Communications, 2020)
Abstract In the face of scientists’ increasing engagement in public discourse, we examine whether facial attractiveness affects their market value (i.e., audience willingness to pay). For a sample of scientists who participate in public speaking, we find that facial attractiveness is uncorrelated with internal academic achievements (as measured by publications and citations) and is only weakly but positively linked to attention outside of academia. Notably, we find that the effect of facial attractiveness on external influence is only robust to measures where speakers’ physical appearance is likely to be most apparent to the public, such as invitations to give TED talks or Google web page counts while the effect on the number of book publications or book awards is not significant. Our results also suggest that these relationships do not differ across scientists’ fields of research. However, we find that in terms of speaking fees, social scientists benefit substantially from being more attractive, whereas unattractiveness is a comparative advantage for natural scientists. A similar divergence in the direction of the relationship between speaking fee and facial attractiveness is also evident for nonacademic speakers from different fields: whereas those from a natural science (job) background gain from unattractiveness, those with a social science history benefit from a beauty premium. This market premium for unattractiveness conforms not only to the common stereotype of the natural scientist but also to a belief that the more unattractive of these researchers engage in higher quality work. Overall, the findings indicate that facial appearance is important in the public perception of academics and, to some extent, their dissemination of knowledge.